Production of Cable Insulation Paper from Pinus kesiya - Guha, S. R. D.; Sharma, Y. K.; Mathur, G. M.; Pant, Rajesh; Jain, D. K. (Indian Forester, 1973)
The suitability of Pinus kesiya grown in Manipur has been investigated for the production of cable insulation paper. The average fibre length in thls species 2.28 mm and average diameter 0.0399 mm. Under the conditions studied at unbleached yield of 55.6 percent on oven-dry chips the breaking length was 8.22 km and tear factor was 148.5. The paper made on the pilot plant was evaluated for electrical properties. The electrical strength was comparable with imported paper. The conductivity of water extract and ash cOntent of the paper was, however, high. This was due to the hard-water used for the manuracture of paper.